Novel Control Scheme to Reduce THD in Bidirectional Three-Phase Inverter Using a Three-Phase Unfolder for the Grid Forming Operation - Celebi, Mehmet; Ertekin, Davut (Wiley, 2025)
Recent trends emphasise the significance of bidirectional power conversion systems in grid-forming operations. Minimising total harmonic distortion (THD) in these systems is crucial for enhancing power quality, efficiency and equipment lifespan. This study proposes a novel reference signal modification control scheme to reduce THD in a bidirectional inverter by adjusting the DC-Link Voltage reference based on AC load feedback. Comparative analysis with conventional systems across various load types demonstrates superior performance, particularly with induction machine loads. The proposed control model involves multiple stages, including error computation, averaging, dynamic error handling, reference modification and regulation using a PI control block. This approach effectively manages error dynamics in the inverter topology and eliminates electromagnetic interference in the PCB without determining any additional theoretical approach. Both simulated and experimental results validate the theoretical analyses, showcasing the efficacy of the proposed method. Its simplicity in modifying the reference voltage makes it suitable for situations where controllers lack the capability to effectively manage desired outputs.
Keywords: adaptive PID controller; bidirectional DC-AC converter; THD; three-phase unfolder